2022
DOI: 10.3390/su142114297
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Heterogeneity of the Recovery of Road Traffic Volume from the Impact of COVID-19: Evidence from China

Abstract: The impact of COVID-19 on traffic volume makes it essential to study the spatial heterogeneity and impact mechanisms of the recovery of road traffic volume to promote the sustainability of related industries. As the research method, this study used a principal component analysis to evaluate the recovery of road traffic volume in China quantitatively, and further conducted an empirical study using a spatial autocorrelation index and a dynamic spatial panel model. The results show that income has a negative impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 95 publications
(106 reference statements)
1
1
0
Order By: Relevance
“…The finding that there is regional heterogeneity [11,12] in road transport resilience under the same external disturbance is consistent with the results of previous research. This result may be related to the differences in epidemic prevention and control measures, travel willingness, and travel demand of residents, which have been analyzed in existing studies [58][59][60].…”
Section: Potential Influencing Factors Of Road Transport Resiliencesupporting
confidence: 92%
See 1 more Smart Citation
“…The finding that there is regional heterogeneity [11,12] in road transport resilience under the same external disturbance is consistent with the results of previous research. This result may be related to the differences in epidemic prevention and control measures, travel willingness, and travel demand of residents, which have been analyzed in existing studies [58][59][60].…”
Section: Potential Influencing Factors Of Road Transport Resiliencesupporting
confidence: 92%
“…Meanwhile, some studies have found that the impact of COVID-19 on road freight has regional heterogeneity [11,12]. However, the existing studies have mainly focused on the external effect of the pandemic on road transport, such as transport demand [13,14], transport capability [15,16], operating transport cost [17], transport performance [18], carbon emission [19][20][21], and the ability of road transport system to resist this impact and maintain its typical performance, which we define as road transport resilience [22,23], is still unclear.…”
Section: Introductionmentioning
confidence: 99%